Improvement of fly ash fusion characteristics by adding metallurgical slag at high temperature for production of continuous fiber. (10th January 2018) - Ma, Zhibin; Tian, Xiuqing; Liao, Hongqiang; Guo, Yanxia; Cheng, Fangqin
Abstract: Combustion in coal-fired power plants generates large amounts of coal fly ash (CFA) solid waste, which is presently under-utilized in China. Replacing natural basalt with CFA as a raw material for producing continuous fiber would not only conserve natural resources and reduces environmental impacts, but also achieve cleaner production of continuous fiber. CFA alone is generally unsuitable for producing continuous fiber, due to its high melting temperature and viscosity. The fusion characteristics of CFA were improved by adding steel (SS) or magnesium (MS) slag (optimal 30%) to meet the technical requirements for producing continuous fiber. Calcium contained in calcium silicates breaks the crystal lattice structure of mullite at high temperature, which leads to the transformation of refractory mullite to fusible anorthite in blends. This provides a theoretical basis for adjusting the fusion characteristics of CFA by adding metallurgical slag. However, adding calcium-containing constituents into CFA promotes recrystallization of amorphous materials in melts during slow cooling, which causes the sharp evolution of viscosity. This would adversely affect fiber production, but can be overcome by adjusting the operational process discussed here. The findings provide the basis for the selection of appropriate materials and technical parameters for producing continuous fiber from industrial solid wastes. Highlights: Coal fly ash and steel/magnesium slag could be used to produce continuous fiber. Formation of anorthite plays a crucial role in producing continuous fiber using fly ash. FactSage calculations were reliable for predicting melting temperature of materials.